Tbe pholcid spiders of Costa Rica (Araneae: Pholcidae) - Huber, Bernhard A (Revista de Biología Tropical, 1997)
Recent studies on the pholcid fauna of Central America have elevated the number of known Costa Rican species from 11 to 28 in only two years. The present paper summarizes the scattered literature and adds two new species as well as three undescribed species, bringing the total number. to 33 species representing seven genera. An illustrated key is presented. An annotated list surnmarizes the information available about taxonomy, morphology and natural history of all known Costa Rican pholcids. The two new species·are Anopsicus tico n.sp. from the Central Valley, and Physocyclus guanacaste n.sp. from the Santa Rosa National Park, Guanacaste. The male of Metagonia hondura Huber, 1997 is described and illustrated for fue first time. Old pholcid records. from Costa Rica are discussed, and types of unsufficiently well described species are redescribed, including all previously known Costa Rican Anopsicus species (A. chiriqui Gertsch, 1982; A. concinnus Gertsch, 1982 ; A facetus Gertsch, 1 982; A. turrialba Gertsch, 1982) as well as Metagonia osa Gertsch, 1986 and M. selva Gertsch, 1986. New localities are given for twelv.e species; of these, four are new for Costa Rica: Anopsicus chiriqui Gertsch, 1982; 'Coryssocneinis' viridescens Kraus, 1955; Physocyclus globosus (TacZanowski, 1873); and Smeringopus pallidus (Blackwall, 1858). The genera Coryssocnemis Simon, 1893 and Smeringopus Simon, 1890 are new for Costa Rica. It is argued that carefully directed· collecting in certain areas and habitatS will probably lead to a further considerable increase in known species.